(untitled) (Research, Society and Development, 2021)
This study aims to identify the knowledge of Community Health Agents (CHA) about the childhood vaccination schedule for children up to five years old. This is a quantitative, descriptive, before-and-after research, with a sample of 25 CHA from two Basic Health Units in Ananindeua-Pará. The average age of CHA is 40 years old; female (64%); 76% check the child’s vaccination card and provide guidance to mothers; 96% said that checking the child’s vaccination card is part of their job; 100% carry out periodic home visits to children in their area, 88% have children with delayed vaccinations in their area. As for the CHA feeling safe to guide mothers about vaccines, there was an increase in the rate from pre to post training (26.1%-73.9%). When asked if they received training in pre and post training, the rate rose from 78.3% to 100%. As for the level of knowledge about vaccines in children up to 5 years of age, there was an increase in pre and post training in the concepts "great" (0%-8.7%), "good" (21.7%-43.5%), “regular” (39.1%-43.5%) and a decrease in the “insufficient” concept (39.1%-4.3%). There was an increase in the average hit rate of the CHA in the pre and post training (61.9%-81.1%) with a difference between the hit rates in the pre and post phases of 19.18%. It is concluded that there is a need for investment in professional qualification of the CHA through permanent education, in order to expand their knowledge about the vaccination calendar.